Organizational models of alternative food networks within the rural-urban interface - Lucia Laginová; Michal Hrivnák; Jana Jarábková (Administrative Sciences, 2023)
Alternative food networks (AFNs) represent local food systems and short supply chain networks alternative to global food systems. These networks are often developed within rural-urban interfaces and take various forms, due to the high propensity towards the innovative organization of the network. The aim of our study is to map the currently applied, distinctive innovative organizational models of alternative food networks by identifying the organizational innovations of these networks in available case studies. Adopting the lens of organizational sociology and using space-filling visualization, the study compares various forms of localized and spatially extended AFNs. The results of our comparative analysis suggest that main aspects of AFNs' differentiation are the models of network organization, applied coordination models, competences structures of the involved actors, nature of the intermediaries and their roles within the AFNs, and the level of customer engagement. Innovation processes within short food networks can be driven by the producer, intermediaries, and communities of consumers. We identified three types of AFNs defined with regard to the predominant direction of flows in the urban-rural interface: (1) AFNs localized within the borders of the city, (2) AFNs based on interconnecting the rural farmers located within rural settlements adjacent to the city and to the consumers in cities, and also (3) AFNs localized in peri-urban interfaces with distant customers.
Keywords: 350; supply chains; alternative food networks; food systems; rural-urban interface; organizational models